The Effect of Noradrenalin Infusion on Plasma and Platelet Lipids and Platelet Function in Man - Nordøy, A; Gjesdal, K; Jaeger, S; Berntsen, H (Thrombosis and Haemostasis, 1975)
Noradrenalin was given as an intravenous infusion in a dosage of 0.1 μg/kg/h over a period of 30 minutes to 5 healthy male subjects. Blood samples were collected before, at the end of and 24 hours after the infusion. A significant increase in the number of circulating platelets and a marked increase of plasma FFA, reflecting an increase of all the main components of the FFA fraction were observed. No significant changes were observed in the similar lipid fraction in platelets and except for a moderate increase in platelet factor 3 activity, no significant changes in other platelet function tests were present.